2021
DOI: 10.1016/j.ijpddr.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the β-tubulin gene family in a benzimidazole-resistant Parascaris univalens population

Abstract: Benzimidazole (BZ) drugs are frequently used to treat infections with the equine ascarid Parascaris univalens due to increasing resistance to macrocyclic lactones and pyrantel. Benzimidazole resistance is rare in ascarids in contrast to strongyle parasites where this resistance is widespread. In strongyles, single nucleotide polymorphisms (SNPs) at codons 167, 198 and 200 in a β-tubulin gene have been correlated to BZ resistance, but little is known about the β-tubulin genes and their po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 67 publications
(98 reference statements)
5
20
1
Order By: Relevance
“…Resistance against macrocyclic lactones, in particular ivermectin, has been reported from Europe, North America, Asia and Australia [ 10 , 12 ]. Resistance to pyrantel [ 2 , 13 ] and benzimidazoles (BZ) [ 14 , 15 , 16 ] has also been reported occasionally. Regarding the pattern of resistance to drug classes, the situation in Parascaris spp.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Resistance against macrocyclic lactones, in particular ivermectin, has been reported from Europe, North America, Asia and Australia [ 10 , 12 ]. Resistance to pyrantel [ 2 , 13 ] and benzimidazoles (BZ) [ 14 , 15 , 16 ] has also been reported occasionally. Regarding the pattern of resistance to drug classes, the situation in Parascaris spp.…”
Section: Introductionmentioning
confidence: 99%
“…Deep amplicon sequencing for the two most widely and highly expressed Ascaris β-tubulin genes revealed no evidence for SNPs associated with BZ resistance [ 43 ]. The β-tubulin repertoire of P. univalens has recently been characterised by Martin et al [ 16 ]. The authors identified a very closely related P. univalens ortholog to almost every Ascaris spp.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations